PERATURAN BUPATI ROKAN HULU PROVINSI RIAU NOMOR 5 TAHUN 2016 TENTANG KEWAJIBAN MENGIKUTI KURSUS PRA-NIKAH - Zahrotul Firdaus; Ita Musarrofa (AL-HUKAMA, 2017)
This article examines the review of Islamic law against regulation of Rokan Hulu District No. 5 of 2016 on pre marriage course. Regent’s regulation No. 5 of 2016 on pre-marriage course is seen under the maslahah mursalah theory. With the course, the prospective husband and wife already have a lot of supplies to deal with various problems that will arise in the future. In addition, the prospective husband and wife are more stable to get marriage because they have already got a lot of knowledge and motivation from pre-marriage courses held by the government of Rokan Hulu Regency. This program also contains elements of avoiding damage, namely divorce which will have a bad consequence for the offspring. Divorce is expected to be avoided by having sufficient knowledge about domestic life, especially the rights and obligations of husband and wife. Besides using maslahah mursalah, this study also uses the theory of saddu al-dzari'ah. The high divorce rate in Rokan Hulu regency is due to several factors, namely the increasingly sophisticated information technology that facilitates infidelity, the unpreparedness of the bride and groom to receive 100 % of their partners post-marriage, economic factors, the lack of knowledge about marriage and the lack of religious education. The various reasons above, especially the problem of the lack of knowledge about marriage can be closed and avoided by the existence of intense marriage supplies. One of the debriefings could be through a pre-marriage course program held by the Regent of Rokan Hulu.